Motion Vector Estimation Search using Hexagon-Diamond Pattern for Video Sequences, Grid Point and Block-Based - S. S. S. , Ranjit; S. K. , Subramaniam; S. I. , Md Salim (International Journal of Simulation, System Science and Technology, 2011)
Grid and block-based motion vector estimation techniques are proposed for motion tracking in video sequences. The grid technique is referred to the hexagon-diamond pattern. While, block-based technique is referred to 16 × 16 pixels of blocks in a single frame in video sequences. The hexagon and diamond pattern is applied onto the 16 × 16 pixels blocks in a single frame for motion tracking purposes in video sequences. The hexagon grid pattern will conduct a search to capture the motion in a particular block of the hexagon region before the diamond grid pattern takes place for the fine search. The diamond grid pattern provides accuracy to obtain the best grid vector coordinate for motion tracking purposes. The hexagon-diamond grid vector coordinate can be used to determine whether the object is moving toward the horizontal or vertical plane. The information determined at grid vector coordinate can be used as a reference when referring to the previous frame in video sequence processing. The grid vector coordinate will help to determine the area of interest to be examined based on the coordinate obtained. Besides the grid vector estimation, the Point Signal Noise-to-Ratio (PSNR) is also applied to measure the quality of the video.